PENGADAAN TANAH UNTUK PEMBANGUNAN GARDU INDUK PLN KECAMATAN PASAR KEMIS KABUPATEN TANGERANG BERDASARKAN UU NO.2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM DAN PERMASALAHANNYA (CONTOH KASUS PUTUSAN NOMOR 642/PDT.G/2017/PN.JKT.SEL) - Rio Aldi; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2021)
In building the public interest, the government will carry out land acquisition. However, sometimes the development for the public interest is not based on land acquisition mechanisms. The South Jakarta District Court Decision Number 642/Pdt.G/2017/PN.Jkt.Sel shows that there are parties who develop public interests that are not based on the land acquisition mechanism, which is there is no compensation and relinquishment of land rights. In this case, PT PLN is an agency that requires the use of physical land that belongs to another party to build an electric substation in Pasar Kemis District, Tangerang Regency. The agreement to build the electric substation is only made through the record of transfer of Physical Use of the Land which is submitted voluntarily. What is the mechanism for land acquisition for the construction of PLN electric Substations based on Law No. 2 of 2012 concerning Land Procurement for Development in the Public Interest Juncto Law No. 30 of 2009 concerning Electricity? How is the legal certainty of the construction of the PLN Electric Substation in Pasar Kemis District, Tangerang Regency on land that has not been released by the holder of land rights? Author uses normative legal research methods and data interviews as supporting data. The results of the research reveal that there is a legal uncertainty in the construction of the PLN Electrical Substation Pasar Kemis District, Tangerang Regency on land that has not been released by the holder of land rights.